Factors influencing consumer's purchase for electrical appliances with SIRIM certification mark / Harsa Ardila Mat Sakim - Mat Sakim, Harsa Ardila (Faculty of Business and Management, 2006)
Consumers make many buying decisions every day. Some of the products are of quality and some are not. This leads to consumers seeking guidelines in making their purchases. This is important to prevent consumers from being cheated by irresponsible traders. Malaysian regulatory body has set electrical appliances as some of the mandatory products that need to be tested and certified by Sirim. This means that they need to get the Sirim Certification Mark. However, not all electrical appliances in the present market have been tested. With increase in trade and a corresponding increase in demand for quality and safety by government authorities, purchasers and consumer, there is a need for a means of providing assurance that a product complies with specified standards or specifications. The Product Certification Scheme aims to provide this confidence through an independent assurance of quality and safety. Consumer's purchases are influenced strongly by cultural, social, personal and psychological characteristics. Somehow, does consumers decision on buying electrical appliances with the SCM influenced by these factors.